In vivo multiclonal transfer of blaKPC‐3 from Klebsiella pneumoniae to Escherichia coli in surgery patients. (5th March 2014) - Gona, F.; Barbera, F.; Pasquariello, A. C.; Grossi, P.; Gridelli, B.; Mezzatesta, M. L.; Caio, C.; Stefani, S.; Conaldi, P. G.; Cantón, R.
Abstract During active surveillance at the Mediterranean Institute for Transplantation and Advanced Specialized Therapies (ISMETT, Palermo, Italy) with the CARBA screening medium, five pairs of Klebsiella pneumoniae carbapenemase (KPC)‐producing K. pneumoniae and Escherichia coli strains were isolated in each of five colonized patients. In each patient, lateral gene transfer was demonstrated by comparing K. pneumoniae and E. coli strains, both possessing KPC‐3, Tn4401a and pKpQIL‐IT elements. The isolates were found to be multiclonal by multilocus sequence typing (sequence type (ST) 512 related to ST258, and ST307 belonging to a clonal complex different from the habitual sequence clone ST258 isolated in Italy) and pulsed‐field gel electrophoresis. The results of our study highlight the easy transfer of KPC among Enterobacteriaceae colonizing the human intestine, and the active and careful surveillance required to identify and prevent the spread of these multidrug‐resistant microorganisms.